Evolução da segurança viária em países participantes da “Década de Ações para a Segurança Viária 2011-2020”: uma análise preliminar - Lima, Marcus Vinícius Gomes de (Universidade Federal de São Carlos, 2020)
In 2011, the United Nations launched the “Decade of Actions for Road Safety 2011-2020” (DASV) with the objective of reducing deaths and injuries caused by traffic accidents in the world by 50%, over ten years. In this sense, it is necessary to evaluate the performance of the countries that presented their proposals to reduce road accidents in order to achieve this goal over the decade. This research has as main objective to raise the actions proposed by the countries that accepted to participate in DASV, plus Brazil, besides comparing the evolution of the road safety indicators among these different nations. Thus, the object of study consists of analyzing the evolution of road accident in this selected group of countries and, for that, the plans proposed by sixteen nations, available in the repository of the World Health Organization (WHO), plus the plan of Brazil, available on a national basis, were identified; based on these plans, all the respective proposals for actions for DASV were obtained. Then, road safety indicators were collected systematically from the official statistical bodies of each country and analyzes of the evolution of road accidents were produced using electronic spreadsheets. The results indicate that four nations (Greece, Austria, Czech Republic and New Zealand) managed to meet the goal of reducing deaths; and six (Egypt, Vietnam, Greece, Czech Republic, Mexico and New Zealand) the goal of injury reduction until the last year of available data in which it is possible to compare all nations (2016 for the number of deaths and 2014 for the number of injuries). Thus, the highlight was Greece, which led the ranking of reduction of deaths from traffic accidents with the value of -48.33%/2016, followed by Austria (-40.30%/2016), Czech Republic (-38.12%/2016) and New Zealand (-36.19%/2016). In the injury indicator, the best result was achieved by Egypt, which had a reduction of -53.80%/2014, followed by Vietnam (-48.11%/2014), Greece (-28.88%/2014), Czech Republic (-28.53%/2014), Mexico (-22.36%/2014) and New Zealand (-20.16%/2014). The negative highlights were the Philippines, which increased the number of deaths (+16.55%/2016), and Brazil, which had the largest increase in the number of injuries (+20.33%/2014).
Evolution of road safety in countries participating in the “Decade of Actions for Road Safety 2011-2020”: a preliminary analysis
Keywords: Acidentes de trânsito; Década de Ações para a Segurança Viária; Segurança viária; Traffic accidents; Decade of Actions for Road Safety; Road safety; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS::ENGENHARIA DE TRANSPORTES; ENGENHARIAS